High ambient temperature effects on the anthropometric status of the population: A systematic review and meta-analysis - Priscila Ribas de Farias Costa; Rita de Cássia Ribeiro-Silva; Rafaela de Oliveira Santos; Karine Brito Beck da S. Magalhães; Ellayne Souza Cerqueira; Aline dos Santos Rocha; Lisianne Passos Luz; Lais Helena Leandro Ribeiro; Otavio T. Ranzani; Ismael Silveira; Maxine Pepper; Enny S. Paixao; et al. (PLoS ONE, 2026)
The effects of high ambient temperatures and heatwaves on health outcomes are well established, yet their impact on nutritional status remains poorly understood. This systematic review and meta-analysis aimed to synthesize current evidence on the association between elevated temperatures and anthropometric indicators in the general population. The protocol was registered in PROSPERO (CRD42024555573), and a systematic search of electronic databases was conducted in September 2025 using terms related to “high temperatures,” “heatwaves,” and “anthropometric indicators.” Twenty studies were included, comprising 2,943,695 participants, predominantly children under five years of age, mainly from Sub-Saharan Africa. Studies demonstrated methodological heterogeneity, with mixed findings for height-for-age (HAZ) and weight-for-age (WAZ), but generally indicated an inverse relationship between high temperatures and anthropometric outcomes. In adults, elevated temperatures were associated with both underweight and obesity, highlighting complex effects on nutritional status. Meta-analyses in children revealed reductions of 0.12 SD in Weight-for-Height Z-scores and 0.03 SD in HAZ per 1°C increase in average temperature. While effect sizes at the individual level appear to be modest, the population-level implications could be considerable given the widespread and increasing exposure to heat. These findings suggest a potential link between thermal stress and nutritional status, underscoring the need for longitudinal and geographically diverse studies to further clarify causal pathways, identify vulnerable groups, and inform evidence-based climate-adaptive public health strategies aimed at mitigating the potential nutritional consequences of rising temperatures.